Acousto-optic light modulation : Broadband fibre-pigtailed acousto-optic frequency shifter. (31st October 2020) - Mazur, M M; Mazur, L I; Ryabinin, A V; Shorin, V N
Abstract: A two-crystal fibre-pigtailed acousto-optic frequency shifter has been developed and investigated. An optimal configuration of acousto-optic cells is chosen. A two-crystal acousto-optic frequency shifter of 785-nm laser radiation in the range from 156 to 196 MHz, with single-mode polarisation maintaining fibres at the input and output, is described. Some recommendations are given how to improve the shifter transmission coefficient and increase the frequency shift range.